Bowled Over by Cricket: Impact of Tape‐Ball Injuries on the Eyes. Issue 1 (January 2017) - Sadiq, Salman Naveed; Ali, Azam; Usmani, Bushra; Ahmad, Khabir
Abstract : Purpose: : The aim of this study was to describe the type and severity of tape‐ball cricket‐related eye injuries seen at a tertiary care hospital. Design: : A descriptive case series. Methods: : This study included all cases of tape‐ball cricket‐related eye injuries presenting to the Section of Ophthalmology, Aga Khan University Hospital, Karachi, from January 2014 to January 2015. Results: : A total of 20 patients with tape‐ball cricket‐related eye injuries were treated during this period. The right eye was involved in most (14/20) of the cases. The commonest presenting symptoms included reduced/blurred vision, ocular pain, redness, and floaters. Sixty percent (12/20) of the affected eyes had a best corrected visual acuity of less than 20/200 at presentation, with the retina being the most commonly involved ocular structure. All patients reported that they were not wearing protective eyewear at the time of trauma. Despite standard management, half of the eyes had severe or total vision loss at the last follow‐up (minimum, 3 months), mainly due to retinal damage. Conclusions: : Our study calls for the compulsory use of protective eyewear by cricket players and for countrywide surveillance data on the true burden of this "unnoticed" preventable cause of unilateral eye injuries and associated vision loss.